The environmental factors that influence success of women entrepreneurs : entrepreneurial intention as a mediator - Nur Sha Azelda Hashim; Mohd Rafi Yaacob; Mohd Nazri Muhayiddin (Faculty of Entrepreneurship and Business,UMK, 2015)
Entrepreneurship typically focuses on identifying opportunities in order to create values for customers, yielding ultimate profit for the founders and investors. It also being a decisive factor which to attain the competitiveness and dynamic character of today’s economic knowledge. However, the Malaysian economic growth and personal propensity shows that women entrepreneurs recently become the most important pool of resources. Based on the Ninth Malaysia Plan it had been stated that there are about half of women in total population, with the increasing of representation at the professional, managerial and technical levels. Increasingly involvement of women entrepreneurs in other country is not only acknowledges and encourages but also influence women entrepreneurs to involve in the business and it has become another opportunity and platform for the women folks to earn an economic income outside of their home based business. Therefore, several studies had identified various factors which indicate the successful woman entrepreneurs based on their performance in business. This study also however, intends to develop a new model that focus on environmental which could influences the successful of women entrepreneurs. Moreover, it’s also highlights the potential role of entrepreneurial intention as a mediator in developing a business and the growth of performance women entrepreneurs, particularly in Malaysia environment. The model was developed by using other studies and previous literatures which do not indicate the mediator which plays an important role of successful women entrepreneurs. This research not only benefits the government and country but also appears an opportunity that can and should be grabbed taken by women entrepreneurs in developing and expanding business widely.